Alternative publishers of books in North America - Anderson, Byron (Library Juice Press, LLC, 2006)
This directory is a unique reference tool that gathers information on significant alternative presses--126 U.S. presses, 19 Canadian, and 18 international presses having either a North American address or distributor. Thirty-three presses are new to this edition.